2017
DOI: 10.1016/j.jash.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Personal-level exposure to environmental temperature is a superior predictor of endothelial-dependent vasodilatation than outdoor-ambient level

Abstract: Environmental temperatures influence cardiovascular physiology. However, the majority of time is spent indoors, making outdoor-ambient temperatures inaccurate estimates of true exposures encountered by most individuals. We evaluated in 50 healthy adults the associations between previous 7-day outdoor-ambient (4 occasions) and prior 24-hour personal-level (2 occasions) environmental temperature exposures with blood pressure, heart rate variability, sleep parameters, and endothelial-dependent vasodilatation (bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Hintsala et al reported that even short-term cold exposure increased central aortic blood pressure [23], and the underlying mechanism may be endothelial-dependent vasodilation [24]. HBP was recently found to be a more powerful predictor than office blood pressure of future cardiovascular events [14).…”
Section: Discussionmentioning
confidence: 99%
“…Hintsala et al reported that even short-term cold exposure increased central aortic blood pressure [23], and the underlying mechanism may be endothelial-dependent vasodilation [24]. HBP was recently found to be a more powerful predictor than office blood pressure of future cardiovascular events [14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rolling average of exposures from 1 to 7 days in duration was calculated. Personal-level exposures and temperatures were recorded as averages for the 24-hour period before the blood draw visit in each study block 23 .…”
Section: Methodsmentioning
confidence: 99%
“…7 Importantly, while chemicals in the air may initiate or potentiate cardiometabolic disease, non-chemical pollutants such as tempera- caused by work strain, grief, or social isolation may co-segregate with air pollution and potentially amplify associations with disease. [8][9][10][11][12] Alterations in vascular function were the earliest pathophysiological mechanism described in response to air pollution exposure in humans, and indeed disturbances in endothelial function are a critical initiating event that is widely relevant to almost all classical risk factors. 13,14 In the present review, we focus on the evidence supporting the impact of air pollution and, its particulate and gaseous constituents on vascular function.…”
Section: Introductionmentioning
confidence: 99%